THE EFFECT OF CONTEXTUAL LEARNING STRATEGY ON THE BASIS OF CLASSROOM LANGUAGE AND LEARNING MOTIVATION ON STUDENTS’ SPEAKING ABILITY - BERA, LAURENSIUS KIAN; HAAN, JOHN; KABELEN, A; HUAN, ELISNA; BILI BORA, D (Postgraduate School, Universitas Nusa Cendana, 2022)
Students' English speaking ability in schools in general is still low. There are various affecting factors. Some most obvious factors include limited English exposure to students in class (classroom language) and students’ motivation to learn English. English language exposure which is very important in foreign language learning is limited. Then, it is necessary to find a strategy which is potential to provide more English language exposure and motivation for students. This study aimed to examine: (1) the difference in speaking ability between students taught with the learning strategy on the bases of classroom language and those taught with conventional learning strategy; (2) the difference in speaking ability between students having high motivation and those having low motivation; (3) interaction effect of the learning strategy on the basis of classroom language and motivation to students' speaking ability. This study used a quasi-experimental research design. In particular, it employed factorial 2x2 version non-equivalent control group. The subjects were the twelfth grade students of SMA Negeri 5 Kupang, Indonesia. Two classes were randomly chosen, one as experimental group and the other as control group. Contextual learning strategy on the basis of classroom language was applied in experimental class whereas conventional learning strategy was used in control class. Data taken from both classes were then descriptively and statistically analyzed (ANOVA) using SPSS version 16.0 for windows. Results showed that (1) there was a significant difference in speaking ability between students in experimental group and those in control group. Contextual learning strategy on the basis of classroom language was more effective; (2) there was a significant difference in speaking ability between students in high motivation group and those in low motivation group. High motivation students were more successful; (3) there was no interaction effect of learning strategy based on classroom language and motivation to students' ability of speaking. Based on these results, teachers of English in general and those teaching at SMAN 5 Kupang in particular are recommended to use classroom language that provides more language exposure and motivation for students.